"Planned Benefits" Can Be Misleading in Digital Transformation Projects: Insights From a Case Study of Human Resource Information Systems Implementation in Healthcare. (June 2020) - Tursunbayeva, Aizhan; Bunduchi, Raluca; Pagliari, Claudia
Human Resources Information Systems (HRIS) are being implemented in many organizations but, like other technology projects, translating their potential benefits into meaningful improvements can be challenging. So-called "planned benefits" approaches are designed to aid this translation, but little is known about their success in HRIS projects. This study examined how a planned benefits approach was manifested in a national-scale HRIS implementation program. The results point to the importance of reviewing the benefits plan at regular intervals, to ensure the project can adapt to changing circumstances, and considering benefits at the level of individual modules and user groups, as well as for the organization as a whole. Adequate data preparation, training, effective communication, and process analysis were identified as key actions necessary for successful HRIS implementation and benefit realization.